Draft Annual Plan 1993-94 Andhra Pradesh Volume-II (Sectoral Programmes) 8. Social Services - Planning Commission (Planning Commission, 1992)
Under this sector an outlay of Rs.2759.40 lakhs was provided in the Budget for 1992-93 and the same outlay has been proposed for the draft annual plan 1993-94 also.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh